PERKEMBANGAN DAN KONTROVERSI TASAWUF FALSAFI DI INDONESIA - Sri Baniah (Jurnal Al-Fatih, 2020)
Abstract: This article aims to examine how the development and controversy of Sufism in Indonesia. Falsafi Sufism has developed quite rapidly in the archipelago, the Islamization of the early generations was colored by the teachings of Sufism, marked by Islam being quickly accepted by the natives who were initially familiar with the mystical Hindu-Buddhist influence. That sufism played a role in that early period was philosophical Sufism which can be categorized as a mystical type of infinity whose manifestation is identical to the wujudiyah development of Ibn Arabi's tajalliyat theory. Along with the development of philosophical Sufism in Indonesia, the teachings of philosophical Sufism have experienced debate and controversy among the Sufis themselves. The debate arose, apart from the difference in the interpretation of Ibn Arabi's doctrine, it was also triggered by differences in the socio-political factors of each of the disputing parties. So that the debate led to groups within it, namely First, groups of supporters of the Wahdat al-wujud understanding; second, groups that oppose the Wahdat al-wujud understanding; and third, the moderate group led by Abd Rauf Singkel. Keywords: Tasawuf, Tasawuf Falsafi, Indonesia